Evaluation of the impact of a nurse-led program of patient self-assessment and self-management in axial spondyloarthritis: results of a prospective, multicentre, randomized, controlled trial (COMEDSPA). (16th October 2020) - Molto, Anna; Gossec, Laure; Poiraudeau, Serge; Claudepierre, Pascal; Soubrier, Martin; Fayet, Françoise; Wendling, Daniel; Gaudin, Philippe; Dernis, Emmanuelle; Guis, Sandrine; Pouplin, Sophie; Ruyssen-Witrand, Adeline; et al.
Abstract: Objective: To evaluate the impact of a nurse-led program of self-management and self-assessment of disease activity in axial spondyloarthritis. Methods: Prospective, randomized, controlled, open, 12-month trial (NCT02374749). Participants were consecutive axial spondyloarthritis patients (according to the rheumatologist) and nurses having participated in a 1-day training meeting. The program included self-management: educational video and specific video of graduated, home-based exercises for patients; and self-assessment: video presenting the rationale of tight monitoring of disease activity with composite scores (Ankylosing Spondylitis Disease activity Score, ASDAS/Bath Ankyslosing Spondylitis Disease Activity Index, BASDAI). The nurse trained patients to collect, calculate and report (monthly) ASDAS/BASDAI. Treatment allocation was by random allocation to this program or a comorbidities assessment (not presented here and considered here as the control group). Results: A total of 502 patients (250 and 252 in the active and control groups, respectively) were enrolled (age: 46.7 (12.2) years, male gender: 62.7%, disease duration: 13.7 (11.0) years). After the one-year follow-up period, the adherence to the self-assessment program was considered good (i.e. 79% reported scores >6 times). Despite a lack of statistical significance in the primary outcome (e.g. coping) there was a statistically significant difference in favor of this program for the following variables: change in BASDAI, number and duration of the home exercises in the active group, and physical activity (international physical activity score, IPAQ). Conclusion: This study suggests a short-term benefit of a nurse-led program on self-management and self-assessment for disease activity in a young axial spondyloarthritis population in terms of disease activity, exercises and physical activity.